Evidence of green leases in England and Wales. Issue 1 (2014) - ,; ,
Abstract : Purpose – This paper aims to report on research that investigates the use of green clauses in leases of office and retail premises in England and Wales.Design/methodology/approach – The authors examined 26 recent leases of green build properties registered at HM Land Registry. The green clauses discovered were classified and compared with the model form green clauses promoted by the London‐based Better Building Partnership's Green Lease Toolkit.Findings – Of the 26 leases analysed, 18 contained some form of green provision.Research limitations/implications – As the sample selected was not representative, a larger study is needed to detect trends in green leasing. This research method does not show the impact of green clauses on property management.Practical implications – This research illustrates the types of clauses that have been used in leases but also shows that green leasing principles are not yet the industry standard. Many new, long leases still make no reference to environmental practices.Originality/value – This is the first research to be done examining the green content of agreed leases and develops a methodology that can be used for future research. Acknowledgements : The authors are extremely grateful to assistance from HM Land Registry in helping them to narrow down titles to obtain copies of, and also from the retailer referred to in this report for supplying them with copies of agreed leases. This research was made possible by a grant from the Research Support Fund, Law Faculty, University of Oxford and research funding from New College, Oxford.